Governance of Tunisian sports organizations: what is the matter? - Ghodhbani, Samir; Souissi, Nizar (Frontiers in Sports and Active Living, 2025)
IntroductionTunisian Sports federations with a public service mission are tasked with organizing, promoting, and developing their respective sports disciplines. Over the last decade, these federations, like other nonprofit organizations, have faced profound challenges regarding their governance methods. This study aims to first explore and categorize the different modes of governance within sports federations and, second, to examine how these governance models impact organizational performance.Design/Methodology/ApproachTo identify and analyze the various governance modes within non-profit sports organizations, adopting a positivist epistemological stance and a hypothetico-deductive approach, this research was conducted on 20 national sports federations, utilizing a questionnaire directed at the president, general secretary, national technical director, and members of the executive committee of each federation. In addition, to analyze the data, an exploratory factor analysis was carried out, allowing for a comprehensive dimensionality check of the variables to test the hypotheses.ResultsThe findings indicate that in 33% of federations, strategic decisions and managerial operations are made through coordination between the various actors. In 24% of federations, a couple or exploded mode of presidential governance prevails. In the remaining federations, the president assumes the role of the sole decision-maker. Paradoxically, the results suggest that regardless of the governance mode in place, all four models positively influence the organizational performance of the federations.DiscussionThis study demonstrates that all four governance models positively impact organizational performance in Tunisian sports federations. However, the strength and nature of these effects vary. The “managerial presidential” and “couple’s presidential” models show relatively stronger associations with performance outcomes, particularly in federations with established professional staff structures. These differences suggest that while each model contributes, their practical effectiveness depends on how clearly responsibilities are distributed and how decision-making is shared among key actors. This paper contributes critical insights into the relationship between governance models and organizational performance in the context of nonprofit sports organizations. The findings suggest that the implementation of an appropriate governance model can lead to significant improvements in both sports results and financial resources. National sports federations, especially members of the executive boards, stand to benefit from adopting governance models that align with their operational needs and strategic goals.